Acceptance and Commitment Training for Ice Hockey Players: A Randomized Controlled Trial - Lundgren, Tobias; Reinebo, Gustaf; Fröjmark, Markus Jansson; Jäder, Emil; Näslund, Markus; Svartvadet, Per; Samuelsson, Ulf; Parling, Thomas (Frontiers in Psychology, 2021)
Recent systematic reviews on the topic of mindfulness- and acceptance-based approaches in sport psychology conclude that there is a need for further trials using a more robust research methodology with direct performance as outcome. Acceptance and Commitment Training (ACT) is a contextual behavioral change method that focuses on facilitating psychological processes such as values, committed action, acceptance and mindfulness. In the present study designed as a randomized controlled trial, 34 junior elite ice hockey players were allocated into either an ACT group intervention or a wait list control group. Results showed significant effects on both objective performance outcomes (goals, assists, and taken shots) and blinded coach ratings of players’ performance, focus and commitment to their development in favor of the ACT group. Effects lasted at 3-month follow-up for the coach ratings, but not for the objective performance measures. All ACT trained players recommended ACT to other players and considered the training as important for their development as ice hockey players. The results add to the growing body of evidence on ACT interventions for athletes and its effect on performance. Future studies should investigate the maintenance of effects from the psychological training over time, using robust research methodology and investigate theoretical coherent potential mediating variables.